Revisiting Caresharing in the Context of Changes in a Florida Retirement Community - Eleanor Krassen Covan (Grounded Theory Review: An International Journal, 2006)
In this paper I revisit the basic social process of caresharing whereby people engage in personal and communal strategies to maximize their pleasure and minimize their losses. I originally discovered caresharing in the context of Hollywood Falls, a Florida retirement community that provided no formal supportive services for its aging residents (Covan, 1998). There, hiding frailty was the most obvious caresharing strategy. In this community which has since become more diverse in terms of ethnicity and age, hiding frailty is no longer practical among the oldest residents. It has been surpassed by bolstering strength, a process which involves exposing need, expanding the caresharing network, stifling crises, and staking competence claims. In consequence of bolstering strength, the oldest residents are able to diminish the costs of help while augmenting opportunities for personal autonomy, thereby extending their period of residence within their ‘independent’ living community.